Assessment of the regional water balance of the limestone subaquifers of Cyprus - Jamal, Aldalou Ahmed A.; Turker, Umut (Indian Acad Sciences, 2015)
The northern part of Cyprus is usually characterized by its small watersheds and the lack of ephemeral surface water resources. Therefore, all the water dependent activities depend on groundwater resources. Kyrenia Range subaquifers are the only natural domestic water supplying sources, fulfilling the required worldwide drinking water quality standards. In the present study, various hydrogeological factors that could influence the aquifer recharge and abstraction are used together with annual groundwater level changes, to estimate the capacity of each subaquifer distributed at the Kyrenia Range randomly. During the analyses, 11 subaquifers are worked out; and their spatial distribution, the depth, and the daily abstraction from the available wells are surveyed. The results show that annual groundwater recharge into the subaquifers is 1126 mm. It is also observed that the subaquifers recharging from the southern foothills are more vulnerable to climate effects than the ones at the northern foothills. The available water storage at the present situation, at each subaquifer, is calculated individually and finally the total storage capacity of Kyrenia Range subaquifers, is assessed as 214 million cubic meters (MCM); whereas the data analyses show that annual abstractions from the 11 subaquifers is 13.34 MCM, annually.
Keywords: Cyprus; evapotranspiration; infiltration; Kyrenia Range; storage capacity; subaquifers